2013
DOI: 10.1371/journal.pone.0055850
|View full text |Cite
|
Sign up to set email alerts
|

Physical Skill Training Increases the Number of Surviving New Cells in the Adult Hippocampus

Abstract: The dentate gyrus is a major site of plasticity in the adult brain, giving rise to thousands of new neurons every day, through the process of adult neurogenesis. Although the majority of these cells die within two weeks of their birth, they can be rescued from death by various forms of learning. Successful acquisition of select types of associative and spatial memories increases the number of these cells that survive. Here, we investigated the possibility that an entirely different form of learning, physical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 40 publications
(79 reference statements)
3
29
0
2
Order By: Relevance
“…Although the data of this study show a lower density of astrocytes in the hippocampus, the quantification of neurons showed that rats trained before cerebral ischemia showed a greater density of neurons compared with the sedentary group. These results can be supported by some studies that demonstrate the benefits of physical exercise in the rescue and recovery of neuronal death in the injured area (Altman and Das, 1965;Curlik and Shors, 2011;Curlik et al, 2013;Ploughman et al, 2007).…”
Section: Discussionsupporting
confidence: 58%
“…Although the data of this study show a lower density of astrocytes in the hippocampus, the quantification of neurons showed that rats trained before cerebral ischemia showed a greater density of neurons compared with the sedentary group. These results can be supported by some studies that demonstrate the benefits of physical exercise in the rescue and recovery of neuronal death in the injured area (Altman and Das, 1965;Curlik and Shors, 2011;Curlik et al, 2013;Ploughman et al, 2007).…”
Section: Discussionsupporting
confidence: 58%
“…Learning a new physical skill can also increase the survival of new neurons in the hippocampus (Curlik et al, 2013; Figure 3). During one such task, a laboratory rodent learns to balance on a rod as it rotates faster and faster during one trial of training.…”
Section: Neurogenesis and Effortful Learningmentioning
confidence: 99%
“…They learn to remain on the rod longer over trials of training (B). Those that are trained retain more newly-generated cells than those that are not trained (Curlik et al, 2013). Those that learn best retain more cells than those that do not learn well (D).…”
Section: Figurementioning
confidence: 99%
“…The positive effect on neurogenesis could be ascribed to forced rotarod running of the animals; then, further enhancement of neurogenesis of Nestorone-treated EAE mice could be due to their improved motor behavior. In this regard, long term exercise such as running, maintains brain function and hippocampus neurogenesis (Marlatt et al, 2012), while physical skills also increase the number of surviving cells in the dentate gyrus (Curlik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%